Effects of cover crops and irrigation on ‘Tempranillo’ grapevine and berry physiology: an experiment under the Mediterranean conditions of Southern Portugal - Tomaz, Alexandra (2021)
In addition to irrigation, other viticultural practices such as soil management can be applied to improve grapevine (Vitis vinifera L.) quality responses and attenuate unfavourable environmental conditions. Cover crops in the interrow of irrigated vineyards change the dynamics of water extraction and it is expected that the patterns of vines’ water relations will be modified, also changing their productive responses. This study took place over two seasons in ‘Tempranillo’ grapevines in a vineyard in South Portugal, where a cover crop was sown in the inter-rows of half the study area (SCC) while maintaining resident vegetation in the remaining (RV). Five water regime treatments were applied: full irrigation (200 mm irrigation amount–I200); moderate irrigation (150 mm–I150); deficit irrigation (100 mm–I100); ultra-deficit irrigation (50 mm–I50); rainfed (I0). Measurements of predawn leaf water potential (ΨPD), stomatal conductance (gs), photosynthetic rate (An), and transpiration rate (E) were made during the final stages of the growth cycle. Data of soil water availability, yield and growth variables, and berries and wine composition were also used. Significant interactions between the effect of soil management and water regime were observed on ΨPD. A water competition effect exerted by the cover crop could be responsible for reduced water loss and carbon assimilation, whenever Spring rain is lower and/or the cover crop biomass development is not controlled. Differences in gs and An observed at midday and late measurements reflect the influence of the daily increase of atmospheric water demand. Stomatal closure of grapevines was less affected in plots of higher soil water storage capacity. The correlation between ΨPD and gs was higher in the midday and late measurements, pointing to the regulation of stomatal response in response to water availability and daily environmental conditions. Principal components analysis (PCA) evidenced an influence of water deficit on metabolic responses that benefit fruit and wine quality. The cluster analysis (CA) revealed that no significant cluster of cases was clearly controlled by soil management or water regime in the first season but, in the second, drier season, significant clustering more irrigation- than soil managementcontrolled showed that a predominant influence of irrigation should be expected for ‘Tempranillo’ grapevines grown under dry Mediterranean conditions